Kemitraan Strategis Non-Zero Sum Game: Hubungan ASEAN-Australia dalam Konteks Geopolitik - Rio Akbar Pramanta; Roihanatul Maziyah; Dela Karisma; Putri Rahma Asri; Ayu Tiara Karel Bua; Dimas Bagas Priambodo; Bayu Mahendra (Universitas Diponegoro, 2018)
ASEAN and Australia has a long history of mutual partnership. It is a strategic foreign policy for both parties. ASEAN needs to maintain its power and influence with their neighboring countries to maintain the political stability in the Southeast Asian region. On the other hand, Australia needs Southeast Asia because it serves as a strategic and crucial pivot of numerous benefits and interests for them, including but not limited to security and economics. However, ASEAN-Australia relations is not separated from the geopolitical implications. The geopolitical factors determine the strategic partnership between ASEAN and Australia, thus leading to the hypothesis in this article where Australia needs ASEAN more than the vice versa, and Australia is the one who benefits more in terms of relative gain, relative to ASEAN.Keywords: ASEAN-Australia relations, neorealism, relative gain, geopolitics